Kompetensi Kepribadian Pendidik Perspektif Pendidikan Islam - Imam Fahrudin (Universitas Muhammadiyah Malang, 2018)
The teacher is the main actor responsible for developing the full potential of students in the education process. The output produced by the educational process certainly depends on the educator as a role model for students. The task of managing the learning process is not easy for an educator. The demands for a teacher's professionalism are proven by a series of competencies that must be mastered. One of the competencies that must be possessed by educators is personality competence. Educator or teacher are figures who are emulated in their knowledge and personality. The problem today is that not a few teachers are less professional in positioning themselves in front of students This study will look for references for teacher personality competencies in an Islamic perspective. The discussion was written through data mining with literature study. The result found seventeen personalities that must be owned by a teacher. Seventeen personality points formulated in this study will form a teacher with a Muslim personality. It also instills Islamic character and is closer to students, so that the teacher will be more successful in managing the learning process.